Traffic management for wired/wireless ATM networks - Li, Yongdong. (2008)
In this thesis, traffic management and flow control issues in the interconnected wired/wireless ATM networks are studied. Various simulation models are established to evaluate the performance of various Explicit Rate (ER) flow control techniques.